Artificial intelligence: The missing link in fighting crimes and insecurity in Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Artificial intelligence (AI) has become an indispensable tool in combating crimes and insecurities especially in developed countries. AI systems have played a prominent role in ensuring the overall security architecture of many countries. Thus, this study investigates how adopting artificial intelligence can help combat crimes and insecurities in Nigeria. The study found that the traditional means of fighting crimes and insecurities in Nigeria have not yielded significant impacts since the rate of crimes and insecurities in the country is still on the increase. Another finding from the study indicated that artificial intelligence has the potential to significantly improve thestate of security in Nigeria by enhancing the speed, accuracy, and efficiency of the country's security operatives. Artificial intelligence can help address crimes and insecurity challenges in the country such as terrorism, piracy, trans-border crime, kidnapping, cybercrime, banditry, Fulani herdsmen–farmer clashes, and other forms of crimes and deviant behaviours. The study also revealed that Artificial intelligence can help in predictive policing, behavioural analysis, content moderation, rehabilitation and support, etc. The study concluded that despite thepositive effects of Artificial intelligence, however, the implementation of Artificial intelligence is not without challenges which include inadequate data, lack of military hardware for possible AI integration, non-existent of knowledge base, etc. Finally, the study recommends the effective integration of AI tools into Nigeria’s security architecture to help tackle crimes and insecurities.
Keywords: Artificial intelligence; Crimes; Insecurity; Nigeria